KEEFEKTIFAN MODEL PEMBELAJARAN COURSE REVIEW HORAY BERBANTU MEDIA VIDEO TERHADAP HASIL BELAJAR TEMA 3 SUBTEMA 1 - Sri Rahayu Hasna; Joko Sulianto; Kiswoyo Kiswoyo (JURNAL SINEKTIK, 2021)
This research is motivated by activities during thematic learning that have an impact on the low learning outcomes of learners. The problem in this study is whether the learning model of course review horay assisted by video media is effective in the learning outcomes of learners theme 3 subthemes 1. This type of research is quantitative research with pre-experimental design research methods with one-group pretest-postesttype. The result of the analysis of t calculated 7.1 ˃ t table 1.7. Based on the average pretest value of 64.3 and postest  75.65. The results of cognitive aspect values at each meeting increased one of them in the interval of values 80-89 with the number of 5 students, the interval of values 90-100 with the number of 15 students. Affective aspects at each meeting experienced an increase, one of which was the value interval of 80-89 with the number of 8 learners and the value interval of 90-100 with the number of 12 learners. Psychomotor aspects with a value interval of 70-79 there are 11 learners and a value interval of 90-100 with the number of 9 students